Evaluation of a Simplified Risk Stratification Twice-Daily Aspirin Protocol for Venous Thromboembolism Prophylaxis After Total Joint Replacement. (August 2020) - Ng, Candy; Zavala, Sarah; Davis, Elissa S.; Adams, William; Pinzur, Michael S.
Objective: To determine using a simplified risk-stratified protocol to select candidates for aspirin therapy have similar death and postoperative complications as universal warfarin therapy in patients undergoing total joint replacement (TJR). Methods: Retrospective cohort study comparing 30-day postoperative outcomes 6 months before and after the implementation of the aspirin protocol (January 1, 2015) in patients undergoing TJR. The control group was comprised of patients using warfarin for VTE prophylaxis. The protocol group included patients who used aspirin 325 mg twice-daily or warfarin if deemed high thrombotic risk or aspirin intolerant by the criteria set forth by the aspirin protocol. Results: This study included 449 patients. No difference was found in the rates of 30-day postoperative bleeding, VTE, death, composite end point of VTE and death, and length of stay between the control and the protocol groups (all P > .05). Thirty-day postoperative surgical site infections (SSIs; 5.8% vs 1.2%; P = .02) and return to operative room (OR; 3.9% vs 0.4%; P = .03) were less frequent in the protocol group. Conclusion: A simplified risk-stratified protocol used to choose patients for aspirin 325 mg twice-daily therapy is safe and effective in patients undergoing TJR, and SSI and return to OR rates may be lower when compared to universal warfarin therapy.